Private adoption of public good technologies: the case of PurpleAir in California - Joshua Graff Zivin; Benjamin Krebs; Matthew Neidell (Environmental Research Communications)
We study the private adoption and spatial diffusion of a technology that provides a local public good—PurpleAir (PA) pollution monitors, which deliver real-time, publicly accessible air quality information. From a purely informational perspective, the ideal spacing of these monitors should reflect the degree of spatial correlation in pollution. We examine whether observed adoption patterns align with an information-maximizing distribution to explore the information implications of this private provision of a public good. Using data from California between 2019 and 2021, we find that monitor adoption is highly clustered in less polluted areas, where the marginal monitor provides minimal additional public information. Moreover, monitor adoption mainly occurs in affluent, predominantly White neighborhoods, underscoring the potential environmental justice concerns associated with the private provision of this public good. Additional analyses suggest that spatial clustering in preferences that are independent of the monitors’ informational value may be driving adoption.